Study of Stacked High Tc Superconducting Circular Disk Microstrip Antenna in Multilayered Substrate Containing Isotropic and/or Uniaxial Anisotropic Materials - Boughrara, A. S.; Benkouda, S.; Bouraiou, A.; Fortaki, T. (Advanced Electromagnetics, 2019)
In this paper, we present a rigorous full-wave analysis able to estimate exactly the resonant characteristics of stacked high Tc superconducting circular disk microstrip antenna. The superconducting patches are assumed to be embedded in a multilayered substrate containing isotropic and/or uniaxial anisotropic materials (the analysis is valid for an arbitrary number of layers). London’s equations and the two-fluid model of Gorter and Casimir are used in the calculation of the complex surface impedance of the superconducting circular disks. Numerical results are presented for a single layer structure as well as for two stacked circular disks fabricated on a double-layered substrate.